Digital transformation : challenges and opportunities : 16th Workshop on e-Business, WeB 2017, Seoul, South Korea, December 10, 2017 : revised selected papers /: challenges and opportunities : 16th Workshop on e-Business, WeB 2017, Seoul, South Korea, December 10, 2017 : revised selected papers. ([2018]) - Unknown
No abstract available